Isolation of a cDNA clone for the murine transplantation antigen H-2Kb. - Reyes, A A (1982)
A library of cloned cDNAs constructed from the poly(A)+RNA of the murine thymoma cell line EL4 (b haplotype) was screened with a probe encoding a short region of the H-2Kb transplantation antigen. One of the clones isolated, pH202, contains a region that can code for a transplantation antigen with an amino acid sequence 98% homologous to that previously published for H-2Kb. Based on this high degree of homology, pH202 appears to encode the H-2Kb antigen from amino acid 66 through the carboxy terminus, including 386 nucleotides of 3'-untranslated sequence. The amino acid sequence deduced from pH202 suggests that the H-2Kb antigen is actually 2 amino acids longer than previously reported (a total of 348 residues). Four other differences in amino acid assignments are seen. Analysis of the DNA sequences of pH202 and other H-2 clones previously described in the literature suggests that alternative routes of splicing at the 3' end of the coding region are involved in the production of different transplantation antigen mRNAs.